Conflict : what has religion got to do with it? : an African-European dialogue. - Goethe-Institut (Accra, Ghana); International Conference on Conflict and Religion (2003 : Accra, Ghana) (Accra : Woeli Pub. Services : Goethe-Institut Accra, 2004)
Lectures and presentations from an international conference on the topic of conflict and religion, which took place in October 2003 and was organized by the Goethe-Institut Accra in co-operation with the Accra Daily Mail.
Human rights and religion : the Christian perspective / Emile Francis Shari (p. 93-102). -- Human rights and religion / Mohammed Halrib (p. 103-113). -- Religion and conflict : synonymous or paradoxical? / Charles Palmer-Buckle (p. 114-124). -- Islam in a post-colonial and conflict-free Ghana : challenges or equilibrium / Mahmoud M Gedci (p. 127-150). -- Islam in post-colonial West African christianized countries / Mensa Obabi (p. 151-156). -- Muslim's communities in multi-religious milieux : some reflections on the Madman Constitution / Samusis Iunido Samusi (p. 159-180). -- Sharia and secular constitutions / Franz Kogelmann (p. 181-192). -- Conflicts -- a perspective on the religious dimensions of the problem / Sheikh J.C Omaye (p. 195-201). -- Instrumentalizing religion in the contest for political power / Georg Brunold (p. 202-208). -- Must the Church involve herself in politics? / Peter K Servong (p. 209-215). -- r (p. 216-224). -- Cultural pluralism, religion and educational philosophy / George P Hagan (p. 227-236). -- Educational systems and the influence of religion / Mauloi Adam (p. 237-241).
Includes bibliographical references.
Keywords: Social conflict -- Religious aspects -- Congresses; Culture conflict -- Religious aspects -- Congresses; Ethnic conflict -- Religious aspects -- Congresses; Islam; West Africa; Conflicts; Conference papers and proceedings; Accra (2003)